1998
DOI: 10.1002/lt.500040512
|View full text |Cite
|
Sign up to set email alerts
|

Combined liver-kidney transplantation in patients with cirrhosis and renal failure: Effect of a positive cross-match and benefits of combined transplantation

Abstract: Patients with renal failure after liver transplantation have a particularly poor prognosis. Therefore, in the setting of end-stage renal disease requiring dialysis or severe renal insufficiency that will not improve after liver replacement, combined liver-kidney transplantation (LKT) is the preferred approach. We have adopted a policy of LKT in patients with end-stage liver disease and renal insufficiency undergoing dialysis or with a creatinine clearance less than 35 mL/min and evidence of chronic renal dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 18 publications
6
45
1
Order By: Relevance
“…In fact, immediately following liver transplantation, kidney transplantation has been safely performed despite the presumed preoperative presence of alloantibody based on preoperative positive cross-match. Previous studies reported that these patients converted to a negative crossmatch after liver transplantation suggesting decreases in alloantibody (6). Based on these clinical observations, it has been proposed that a liver allograft protects the kidney from hyper acute rejection by either absorbing or neutralizing DSA.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, immediately following liver transplantation, kidney transplantation has been safely performed despite the presumed preoperative presence of alloantibody based on preoperative positive cross-match. Previous studies reported that these patients converted to a negative crossmatch after liver transplantation suggesting decreases in alloantibody (6). Based on these clinical observations, it has been proposed that a liver allograft protects the kidney from hyper acute rejection by either absorbing or neutralizing DSA.…”
Section: Introductionmentioning
confidence: 90%
“…Early acute kidney rejection rates in combined transplantation are on average less than 10% (Table 10). 12,42,43,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]65,80 This is compared with rejection rates of 30% to 50% reported in the literature for temporally matched kidney-only transplant recipients. 65 Thus, even with less HLA matching and a positive cross-match, renal rejection rates appear to be lower when a liver allograft is placed concurrently ( 3).…”
Section: Allograft Rejection After Lktmentioning
confidence: 99%
“…81,82 The pathophysiological cause of this effect has not been identified; however, it has been observed that positive pretransplantation cross-matches become negative after placing the new liver, providing support for the theory that liver allograft absorption of anti-HLA antibodies protects the kidney. 47,51,53,61,82 Neutralization of anti-HLA antibodies and cytotoxic lymphocytes by liver allograft production of soluble HLA molecules also may contribute. 83 Last, it is possible that passenger leukocytes within the liver result in greater microchi- merism than after kidney-only transplantation, with the subsequent development of tolerance.…”
Section: Allograft Rejection After Lktmentioning
confidence: 99%
“…(1,3,(9)(10)(11). The complete removal of HLA antibodies by the liver allograft converting a crossmatch from positive to negative during combined a liver-kidney transplant has been reported (12). However, the long-term beneficial effect of the liver in combined liver-kidney transplants has been debated (13).…”
Section: It Is Widely Appreciated That the Liver Is Resistant To Antimentioning
confidence: 99%